EP.TU.193Omental band - A unusual cause of mechanical small bowel obstruction in a virgin abdomen. (28th October 2021) - Loganathan, Santhosh; O'Connor, Adam; Singh, Amal; Fani, Mazyar
Abstract: Introduction: The small bowel obstruction in a non-operated abdomen is rare, and the most common causes are hernia and neoplasm. The complete mechanical small bowel obstruction due to an omental band in a patient with no previous abdominal surgery is rare, and less than five cases have been reported in the literature. Case presentation: We report a 65 year old male patient presented to the emergency department with complaints of abdominal pain, distension, vomiting and obstipation for four days. On clinical examination, his abdomen was distended, diffusely tender, guarding. The blood investigations showed elevated White blood cells and neutrophils with normal CRP and the Serum lactate. The Abdominal X-ray was suggestive of SBO. The Computed tomography of the abdomen and pelvis showed marked dilatation of the jejunum, the ileum is entirely collapsed, the impression of a double beak sign in the mid-abdomen which would suggest closed-loop obstruction due to a possible internal hernia. We proceeded with emergency diagnostic laparoscopy converted to laparotomy, which showed omental band causing closed-loop proximal small bowel obstruction. The bowel loops appeared congested with the constriction band due to omental band. The omental band was divided, and the obstruction was relieved. Postoperatively patient recovered well and was discharged on day three post-op. Discussion: The timely diagnosis and intervention could prevent complications like strangulation, ischemia and gangrene. Though the omental band is rare, it should still be suspected as an aetiology in patients without prior abdominal surgery.